A case of mania presenting with hypersexual behavior and gender dysphoria that resolved with valproic acid - Michelle R. Heare; Maria Barsky; Lawrence R. Faziola (Mental Illness)
Hypersexuality and gender dysphoria have both been described in the literature as symptoms of mania. Hypersexuality is listed in the Diagnostic and Statistical Manual of Mental Disorders 5 as part of the diagnostic criteria for bipolar disorder. Gender dysphoria is less often described and its relation to mania remains unclear. This case report describes a young homosexual man presenting in a manic episode with co-morbid amphetamine abuse whose mania was marked by hypersexuality and the new onset desire to be a woman. Both of these symptoms resolved with the addition of valproic acid to antipsychotics. This case report presents the existing literature on hypersexuality and gender dysphoria in mania and describes a treatment option that has not been previously reported.